Peran Konselor dalam Meningkatkan Adaptabilitas Karier Remaja untuk Meghadapi Peluang dan Tantangan Era Society 5.0 - Alivia Eka Arianti; Burhani, Iqbal Khoirul; Diniyah, Usrotun; Alamsyah, Muh. Nur (Sehati Abdimas, 2023)
The aim of this research is to determine the role of guidance and counseling teachers in improving the career adaptability of teenagers, which is still low in Indonesia. In this case, the role in question is optimizing the guidance and counseling service strategy and the competencies that guidance and counseling teachers need to have in responding to the challenges and opportunities of the society 5.0 era. In facing the era of society 5.0, the projected educational curriculum has mentioned several main points, namely, character education, the ability to think critically, creatively and innovatively, and the ability to apply technology in this era. In line with the projected education curriculum in Indonesia, there are several challenges in facing the era of society 5.0. One of them is teenagers' unpreparedness in facing career challenges in the future. In this era, teenagers need to have sensitivity in facing challenges into opportunities. One effort that can be made is to increase career adaptability. Career adaptability is an individual's readiness to cope with predictable tasks at work, as well as being able to overcome unexpected situations that may arise as changes in his work conditions. This research uses a qualitative approach with the library research method. The results of this research explain several service strategies that can be implemented by counselors, including involving the use of technology in the guidance process, developing relevant training and education programs, as well as collaborating with related parties to prepare teenagers to face the Society 5.0 era. Apart from that, increasing the competency of guidance and counseling teachers must also be considered so that guidance and counseling teachers can provide the best service to students, especially teenagers, in order to increase the career adaptability of teenagers.